2012
DOI: 10.1002/app.36431
|View full text |Cite
|
Sign up to set email alerts
|

Online conductivity and stability in the emulsion polymerization of N‐butyl methacrylate: Nonreactive versus reactive systems

Abstract: Two different types of conductivity probes, that is, a torroidal probe and a resistance probe, were used as online sensors to monitor conductivity during the course of emulsion polymerizations of n‐butyl methacrylate (BMA). These measurements were first applied to a nonreactive system, but the results showed that this method cannot be used to monitor latex stability in this system. Batch emulsion polymerizations of BMA were then carried out using different concentrations (0.6, 1.2, 2.4, and 7.8 mM) of sodium l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 8 publications
0
15
2
Order By: Relevance
“…The initial conductimetric data obtained from the emulsion polymerization of butadiene exhibited an interesting behavior that was different from the behavior expected. One of the differences was related to the beginning of the reaction at which conductivity has an ascending behavior, while the other experiments performed in our previous study and the results reported in the literature showed that the beginning of the reaction is associated with a decrease in conductivity . The other important difference was regarding the status of the minimum of conductivity such that the minimum occurs within a short period of time, unlike the other emulsion polymerizations.…”
Section: Introductioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The initial conductimetric data obtained from the emulsion polymerization of butadiene exhibited an interesting behavior that was different from the behavior expected. One of the differences was related to the beginning of the reaction at which conductivity has an ascending behavior, while the other experiments performed in our previous study and the results reported in the literature showed that the beginning of the reaction is associated with a decrease in conductivity . The other important difference was regarding the status of the minimum of conductivity such that the minimum occurs within a short period of time, unlike the other emulsion polymerizations.…”
Section: Introductioncontrasting
confidence: 54%
“…The conductimetric data reported in the literature for emulsion polymerizations containing an ionic surfactant and an ionic initiator show that the beginning of the reaction is associated with a decrease in conductivity because the nucleation and growth of the particles result in the absorption of the surfactant and initiator from the aqueous phase . The reported data represent that conductivity passes a minimum and begins to rise because of the dominance of coagulation over the nucleation and growth of the particles.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…An advantage of the redox initiator system is that free radicals can be generated from reduction–oxidation reactions at low temperatures. In this research, a model emulsion system comprised of n ‐butyl methacrylate ( n ‐BMA), sodium lauryl sulfate (SLS), water, and other ingredients was used to study the difference in nucleation mechanism between redox and thermal initiators.…”
Section: Introductionmentioning
confidence: 99%
“…Emulsion stability refers to the ability of an emulsion to resist changes in its physicochemical properties over time . A wide variety of different methods have been developed to determine emulsion stability, including visual inspection, photodensitometry, centrifugation, electrical conductivity, droplet counting, light scattering, droplet lifetime, and others . These important analytical methods including their operating principles and range of application are well reviewed by McClements .…”
Section: Introductionmentioning
confidence: 99%